Combined X‐ray and neutron single‐crystal diffraction in diamond anvil cells. Issue 1 (28th November 2019) - Grzechnik, Andrzej; Meven, Martin; Paulmann, Carsten; Friese, Karen
Abstract : It is shown that it is possible to perform combined X‐ray and neutron single‐crystal studies in the same diamond anvil cell. The data processing procedures and a joint structural refinement of the high‐pressure synchrotron and neutron single‐crystal data are presented and discussed for the first time. Abstract : It is shown that it is possible to perform combined X‐ray and neutron single‐crystal studies in the same diamond anvil cell (DAC). A modified Merrill–Bassett DAC equipped with an inflatable membrane filled with He gas has been developed. It can be used on laboratory X‐ray and synchrotron diffractometers as well as on neutron instruments. The data processing procedures and a joint structural refinement of the high‐pressure synchrotron and neutron single‐crystal data are presented and discussed for the first time.